2013
DOI: 10.9755/ejfa.v25i2.7151
|View full text |Cite
|
Sign up to set email alerts
|

Agronomic and physiological responses of pearl millet ecotype (Pennisetum<br>glaucum (L.) R. Br.) to saline irrigation

Abstract: The objective of this study was to identify morphological and physiological traits for salinity tolerance in Tunisian autochthonous ZZ pearl millet ecotype (Pennisetum glaucum (L.) R. Br) under local conditions. ZZ ecotype was cultivated under different levels of salinity and growth parameters, water relations and mineral content were measured. Results showed that ZZ pearl millet ecotype was unable to store the large amounts of salt in the leaves, while maintaining high leaf water content and without a grave c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
5
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 43 publications
2
5
1
Order By: Relevance
“…Maximum free radial scavenging potential was shown by the pearl millet cultivated in Rejiche (84.78%) whereas the minimum scavenging potential was found in Kelibia (22.71%). These results were in the same range of those obtained with other Tunisian pearl millet, 41 but they were higher than those obtained with Indian landraces. 42…”
Section: Dpph Radical Scavenging Activitysupporting
confidence: 83%
See 3 more Smart Citations
“…Maximum free radial scavenging potential was shown by the pearl millet cultivated in Rejiche (84.78%) whereas the minimum scavenging potential was found in Kelibia (22.71%). These results were in the same range of those obtained with other Tunisian pearl millet, 41 but they were higher than those obtained with Indian landraces. 42…”
Section: Dpph Radical Scavenging Activitysupporting
confidence: 83%
“…This high content of polyphenols of pearl millet has been elucidated previously. 40,41 These results were by far higher than those obtained for other pearl millet cultivars grown in India 42,43 but lower than that obtained from South African pearl millet, 44 and in the same range as those cultivated in Nigeria. 45 The total flavonoid components (TFC) of different pearl millets differed significantly (P < 0.05).…”
Section: Agro-morphological Variationcontrasting
confidence: 60%
See 2 more Smart Citations
“…Yakubu et al T (2010) reported that, plant height, shoot and root dry weights of five pearl millet varieties were significantly decreased with increasing soil salinization. Also, Leila Radhouane (2013) used three levels of saline water irrigation, T 1 (1g NaCl/l as control), T 2 (4g NaCl/l) and T 3 (7g NaCl/l) for pearl millet plants, noticed that plant height of T 3 was 18% significantly lower than T 1 and 13% than T 2 . The same findings were noticed by Abd El-Rahman et al (2005), Hussein et al (2010) and Siti Aishah et al (2011) on sorghum.…”
mentioning
confidence: 99%